Sulh: an alternative dispute resolution and amicable settlement of family dispute - Ahmad, Sa'odah (Yayasan Dakwah Islamiah Malaysia (YADIM), 2015)
The first part of the paper seeks to examine the definition and authorities of sulh as provided by the Qur’an and hadith of the Prophet Muhammad SAW. The practice of sulh in resolving family disputes will also be briefly discussed. The advantageous of sulh based on some previous research findings will be highlighted in the last part of the paper. The paper concludes that sulh is a viable mechanism in resolving disputes amicably which is very pertinent in family disputes (for the purpose of preserving good relationship among the disputants).